Determinants of Indonesia’s Foreign Exchange Reserves Using the Monetary Approach to the Balance of Payments (MABP) - Prasetyo, Alvin Sugeng; Listiana, Yufita (Universitas Batanghari Jambi, 2025)
This study aims to analyze Indonesia's foreign exchange reserves using a monetary balance of payments approach. The data used are quarterly time series data for the period 2010.Q1 – 2024.Q4. The method used is FMOLS. The results show that real interest rates and domestic credit have a negative and significant effect on foreign exchange reserves. However, in contrast, economic growth and the real exchange rate have a positive and significant effect on Indonesia's foreign exchange reserves during the period 2010 – 2024.